α-Carboxy-β-Lactones from Photoinduced Ring Contraction of 3-Diazodihydrofuran-2,4-diones - Beneke, Julia; Schobert, Rainer (Synthesis, 2013)
β-Lactones were prepared by irradiation of 3-diazodihydrofuran-2,4-diones via Wolff rearrangement proceeding with retention of the configuration of the migrating carbon atom. In the presence of alcohols or thiols, but not amines, the corresponding 3-(alkoxycarbonyl)- or 3-[(alkylsulfanyl)carbonyl]-β-lactones were obtained. 5-Alkyl-3-diazodihydrofuran-2,4-diones gave exclusively trans-3,4-disubstituted β-lactones.
Keywords: tetronic acids; β-lactones; ring contraction; rearrangement; diazo compounds